Two test-cases for synergistic detections in the Martian atmosphere: Carbon monoxide and methane. (March 2017) - Robert, S.; Camy-Peyret, C.; Daerden, F.; De Mazière, M.; De Wachter, E.; Neary, L.; Vandenbussche, S.; Vandaele, A.C.
Abstract: In the frame of the scientific preparation of ExoMars Trace Gas Orbiter (EMTGO), synergistic retrievals were performed on synthetic spectra of two different remote sensing instruments of the Martian atmosphere. To benefit from their diversity, we have simulated spectra of a Fourier transform spectrometer (FTS), working in the middle to far infrared and of a grating spectrometer (GA) working in the middle infrared. As control runs, non-synergistic retrievals were performed as well. Two molecules of interest in the Martian atmosphere were chosen to test this method: carbon monoxide and methane. Scenarios were selected and two different vibrational bands for each molecule were used to retrieve molecular volume mixing ratios. Synergistic retrievals for CO are useful both in solar occultation and in nadir, while for CH4, the concentration of which is expected to be very low, the results for FTS and GA in synergy are not as conclusive due to the weak signal in the ν4 vibrational band (covered by FTS) compared to the stronger ν3 band (covered by GA). Our results represent a first step to an optimized use of infrared spectra to be recorded in Martian orbit by two instruments of EMTGO. Highlights: Proof of concept of synergistic retrievals is demonstrated. Best parameter sets are found for different types of retrievals both in solar occultation and nadir geometries. Importance of the appropriate spectral features and spectroscopic parameters are highlighted.